Preparation and characterization of a thermoplastic proton-exchange system based on SEBS and polypropylene blends - K. Polat; M. Sen (eXPRESS Polymer Letters)
The paper focuses on a series of blends prepared with different contents of polystyrene-block-poly-(ethylene-ranbutylene)-block-polystyrene (SEBS) and polypropylene (PP) for the purpose of examining the potential as proton exchange membranes. Polymer blends were prepared by twin-screw extrusion and then compressed by means of a hot-press device into thin films of 125 µm and then ionic sides were created by solid state sulfonation in a chlorosulfonic acid solution. Obtained films were characterized by means of water-uptake, mechanical properties, ion-exchange capacities (IEC) and ion conductivities. It was observed that the rigidity of the films increased with rising sulfonation durations. However humidity absorption from the air decreased the rigidity at high sulfonation levels. Improved water uptake values were obtained when compared to previously reported values in the literature. On the other hand ion exchange values showed an increase parallel to the sulfonation duration up to 45 minutes, but a decrease thereafter was observed due to the diffusion of some sulfonated polymer chains into the ion-exchange medium thereby calculated ion exchange values of S-SEBSH45 and S-SEBSH60 were found less than expected. All films showed ion conductivities up to 432 mS/cm at 25 °C. Only S-SEBSH45 and S-SEBSH60 were successful in conducting protons at 80 °C owing to the high water retaining capacity.